Quantitative Mapping of the East Australian Current Encroachment Using Time Series Himawari‐8 Sea Surface Temperature Data. Issue 10 (7th October 2020) - Xie, Senyang; Huang, Zhi; Wang, Xiao Hua; Leplastrier, Aero
Abstract: The East Australian Current (EAC) is a highly dynamic western boundary current that exerts significant influences on the marine ecosystem off southeast margin of Australia. For the first time, a quantitative mapping of the EAC system was conducted using Himawari‐8 sea surface temperature data and a Topographic Position Index (TPI)‐based image processing technique. The validation using Bluelink ReANalysis data suggested good reliability of our mapping results. Subsequent quantitative examination provides new insights into the EAC's cross‐shelf movement which is a driving force of adjacent slope‐shelf circulations. Along the coast of New South Wales (NSW), large‐scale and high‐frequency EAC encroachment was observed, being every 60–80 days upstream (30–32°S) and every 90–100 days downstream (33–35°S), which is associated with the EAC's intrinsic oscillation and eddy shedding. Downstream, the EAC encroachment exhibits a 20‐day longer period and a double amplitude. Such dephasing is most likely due to the abrupt change of regime at the EAC separation point (32–33°S). Upstream, the EAC encroachment also exhibits seasonality, being 10–15 km closer to the coast in austral summer, which is due to the seasonal EAC broadening. Higher‐frequency (16–32 days) and smaller‐magnitude EAC intrusion was observed along the entire NSW coast (28–37°S), which is possibly associated with EAC's meanders and frontal eddies. In the extension zone (37.30–44°S), we observed maximum EAC encroachment in summer, which is an expression of the seasonal boundary flow off eastern Tasmania. A data set of EAC encroachment (2015–2017) is available (see Data Availability Statement). Plain Language Summary: The East Australian Current (EAC) frequently intrudes landward, drives coastal water uplift, and consequently brings nearshore nutrient blooms. Such current intrusions therefore exert significant impacts on the coastal marine ecosystem. To thoroughly examine the EAC intrusions, first, we developed an accurate mapping of the EAC using satellite imagery. Next, using the mapping products, we directly measure and investigate the time‐varying spatial closeness between the EAC and the coast. Our results show that the EAC is a highly dynamic and unstable eddy‐current system which intrudes landward all year round with multiple periods and scales. The semiautomatic mapping presented here has many practical applications in measuring, monitoring and tracking of ocean currents and eddies. Key Points: For the first time a quantitative mapping of a highly dynamic WBC system is created using imagery technique on satellite SST data Direct evidences confirm that the EAC is an unstable eddy‐current system which encroaches onshore with multiple frequencies and amplitudes Our semiautomatic mapping has many practical applications in measuring, monitoring and tracking of ocean currents and eddies